Communities of Practice : An Alaskan Native Model for Language Teaching and Learning - Siekmann, Sabine; Marlow, Patrick E., 1966- (Book collections on Project MUSE., 2013)
This book describes an innovative project in native-language instruction that has wide applicability in second-language classrooms. Although the project it describes was developed in Alaska, the program can serve as a model throughout the world.